Strategies and outcomes of involving university students in community engagement: an adaptive leadership perspective - Hlalele, Dipane; Manicom, Desiree; Preece, Julia; Tsotetsi, Cias T. (Council for the Development of Social Science Research in Africa (CODESRIA), 2015)
The purpose of this article is to compare how students and community members learned and applied their knowledge in four small-scale university–community engagement projects during 2013. It draws on the concept of adaptive leadership as an approach and analytical tool in a recently completed community engagement and service learning action research partnership between the University of the Free State (UFS) Qwa Qwa campus and the University of KwaZulu-Natal (UKZN) Pietermaritzburg campus. The project was funded by the National Research Foundation, with additional support from the UKZN Teaching and Learning Fund and UFS Faculty of Education research funds. A total of twelve case studies involved sixty-five students, nine NGOs and four schools. In each case, students worked in teams in response to community requests for assistance. Projects included Saturday curriculum activities for schools, workshops for parents, assisting with film making or archiving, assisting with monitoring and evaluation of rural reading clubs, producing small organic gardens and assisting with a childcare development project. Each case study involved end of project interviews with students and community contacts and some interim observations during the project implementation phase. This article compares four of the case study findings between the two institutions. It outlines how the concept of community engagement has evolved and briefly reviews the literature on community engagement, particularly in the South African context. It then introduces the theoretical framework and methodology. The findings suggested that the adaptive leadership approach contributed to stimulating shared ownership of learning.

Le but de cet article est de comparer la façon dont les étudiants et les membres de la communauté ont appris et appliqué leurs connaissances dans quatre projets à petite échelle sur l’engagement communautaire des universités en 2013. Il se fonde sur le concept de leadership adaptatif en tant qu’approche et outil d’analyse dans le cadre d’un projet récemment achevé de recherche-action sur l’engagement communautaire et l’apprentissage par le service communautaire, mené dans un partenariat entre le campus Qwa Qwa de l’Université de l’État-Libre (UFS) et le campus Pietermaritzburg de l’Université du Kwa Zulu-Natal (UKZN). Le projet a été financé par la « National Research Foundation » (Fondation nationale de la recherche) avec le soutien de l’« UKZN Teaching and Learning Fund » (Fonds d’éducation et de formation de l’UKZN) et les « UFS Faculty of Education research funds » (fonds de recherche de la Faculté de l’éducation de l’UFS). Au total, douze études de cas ont impliqué soixante-cinq étudiants, neuf ONG et quatre écoles. Dans chaque cas, les étudiants ont travaillé en équipe pour répondre aux demandes d’assistance communautaires. Cet article compare les deux institutions par rapport à quatre des résultats de l’étude de cas. Il décrit comment le concept d’engagement communautaire a évolué et fait brièvement la revue de la littérature sur ledit concept, en particulier dans le contexte sud-africain. Il présente ensuite le cadre théorique et la méthodologie. Les résultats suggèrent que l’approche de leadership adaptatif a stimulé l’appropriation partagée de l’apprentissage.
Keywords: Community engagement